Do mnemonics help healthcare professionals learn and recall cholinergic toxidromes?. (3rd July 2022) - Hurst, Nicholas B.; Grossart, Elizabeth A.; Knapp, Shannon; Stolz, Uwe; Groke, Steve F.; Solem, Casey R.; Williams, Amy; French, Robert N. E.; Appel, Joshua E.; Walter, Frank G.
Abstract: Background: The U.S. National Library of Medicine and Department of Homeland Security assembled subject matter experts (SMEs) for the Toxic Chemical Syndrome Definitions and Nomenclature Workshop. The SMEs at this meeting identified a lack of research evaluating the effectiveness of field recognition of toxidromes to guide treatment. They suggested that mnemonics may be helpful for remembering and recognizing toxidromes and further, that rapid toxidrome recognition, through use of a mnemonic or otherwise, leads to rapid action and urgent intervention. Objectives: (1) Determine if published studies demonstrate HPs can learn and recall hazardous materials (hazmat) toxidromes. (2) Determine if Healthcare Professionals (HPs) can learn mnemonics for muscarinic and nicotinic toxidromes during the Advanced Hazmat Life Support (AHLS) Provider Course (PC) and recall these cholinergic mnemonics when retested years later. Our hypothesis is HPs can learn these mnemonics and recall them up to four years later. Methods: We analyzed results of HPs who completed AHLS PC pre-tests and post-tests during their initial AHLS PC between March 1, 2007 and March 1, 2010, and then, within four years, took either an online retest or a pre-test for a second AHLS PC. We compared pre- and post-test answers for questions regarding muscarinic and nicotinic mnemonics to assess if HPs can learn these mnemonics during an initial AHLS PC and then recall these mnemonics later, during retesting. We compared the percentage of HPs who correctly identified each cholinergic mnemonic on the pre-test, post-test, and retest using McNemar's test for paired, nominal data. We searched six literature databases to see if there were any previous similar studies. Results: Our literature search found no similar published studies. The mean time to re-testing was 3.6 years (SD 0.8 year). The percentage of respondents correctly answering the question for the muscarinic toxidrome was 53% on the pre-test, 100% on the post-test, and 75% on the retest. The percentage of respondents correctly answering the nicotinic toxidrome question was 52% on the pre-test, 100% on the post-test, and 77% on the retest. Conclusion: All studied healthcare professionals learned the cholinergic toxidrome mnemonics during their initial AHLS PC. Mnemonic recall declined somewhat on retesting; however, recall was evident in 75–77% of retest takers compared to their pre-test results up to four years earlier, a statistically significant difference ( p  < .001) for both mnemonics. This supports our study hypothesis that HPs can learn these mnemonics and recall them up to 4 years later.